Extension of the Period for Consent to Increase Quotas Under the Fourteenth General Review of Quotas, the 2008 Reform of Quota and Voice, and the Eleventh General Review of Quotas. (Policy Papers; Policy Paper ;, 2015)
This paper proposes a further six-month extension of the period for consent to increase quotas under the Fourteenth General Review of Quotas. The current deadline is due to expire on December 31, 2015, however, Board of Governors Resolution No. 66-2 provides that the Executive Board may extend the period for consent as it may determine. An extension under Resolution No. 66-2 will also extend the periods of consent for quota increases under the 2008 Reform of Quota and Voice (Resolution No. 63-2) and the Eleventh General Review of Quotas (Resolution No. 53-2). As of December 14, 2015, 21 members have not yet consented to their proposed quota increases under Resolution No. 66-2 (see Appendix I). Once the conditions for effectiveness of the individual quota increases are met, members may then pay for their quota increases to make them effective.